The first report of two parasitoids braconids wasps on sugar beet moth, Scrobipalpa ocellatella Boyd. (Lep.: Gelechidae) from Khorasan-e-Razavi province - J. Mahmudi (Sugar Beet Seed Institute, 2013)
The sugar beet moth, Scrobipalpa ocellatella Boyd. (Lep.: Gelechidae( is the specific pest of beet. The aim of the present study was to identify the parasitoids of the moth. Therefore, sampling was conducted in fields of Khorasan-e-Razavi Province, Iran from early July until October in 2010. Larvae and pupa were collected along with tubers of sugar beet and then, they were reared under controlled conditions, 25±2°C, 65±5% relative humidity and 14:10 day/night duration until the emergence of parasitoid adults. Tubers were investigated daily and the emerged parasitoids were collected. These parasitoids were put in alcohol 75%. In this study, two species of larval parasitoids were collected and identified including Bracon intercessor Nees and Microchelonus subcontractus Abdinbekova both of which belong to Braconidae family. B. intercessor is larval parasitoid and M. subcontractus is larva-pupal parasitoid. Paratype samples of the collected parasitoids are maintained in Laboratory of Entomology, Shahed University of Tehran, Iran.